Is It Hepatotoxicity? Isolated AST Elevation During Isotretinoin Therapy in an Adolescent - Varshita Chirumamilla; Rachel E. Tao; Leah Lalor; Alexis J. Gumm (Pediatric Dermatology, 2026)
ABSTRACT This report describes a 14‐year‐old female undergoing isotretinoin therapy for severe acne who developed a persistent isolated elevation of aspartate aminotransferase (AST) with normal alanine aminotransferase (ALT), creatine kinase (CK), triglycerides, and no systemic or gastrointestinal symptoms. A focused evaluation, including medication and alcohol history review, complete blood count (CBC), and muscle and hepatic markers, showed no evidence of clinically significant hepatic, muscular, or hematologic abnormalities. Given the stable isolated pattern and reassuring workup, isotretinoin was continued without interruption, and the findings were most consistent with a benign macro‐AST phenomenon. This case highlights a structured approach to isolated AST elevation during isotretinoin therapy and supports consideration of macro‐AST after appropriate evaluation and exclusion of alternative causes.